Urokinase mediates fibrinolysis in the pulmonary microvasculature - Bdeir, Khalil; Murciano, Juan Carlos; Tomaszewski, John; Koniaris, Lauren; Martínez, José; Cines, Douglas B.; Muzykantov, Vladimir R.; Higazi, Abd Al-Roof (My University, 2000)
The role of urokinase-type plasminogen activator (uPA) and its receptor (uPAR) in fibrinolysis remains unsettled. The contri bution of uPA may depend on the vascu lar location, the physical properties of the clot, and its impact on tissue function. To study the contribution of urokinase within the pulmonary microvasculature, a model of pulmonary microembolism in the mouse was developed. Iodine 125 (125I)¿ labeled fibrin microparticles injected intra venously through the tail vein lodged preferentially in the lung, distributing ho mogeneously throughout the lobes. Clear ance of 125I-microemboli in wild type mice was rapid and essentially complete by 5 hours. In contrast, uPA2/2 and tissue-type plasminogen activator tPA2/2 mice, but not uPAR2/2 mice, showed a marked im pairment in pulmonary fibrinolysis throughout the experimental period. The phenotype in the uPA2/2 mouse was res cued completely by infusion of single chain uPA (scuPA). The increment in clot lysis was 4-fold greater in uPA2/2 mice infused with the same concentration of scuPA complexed with soluble recombi nant uPAR. These data indicate that uPA contributes to endogenous fibrinolysis in the pulmonary vasculature to the same extent as tPA in this model system. Bind ing of scuPA to its receptor promotes fibrinolytic activity in vivo as well as in vitro. The physical properties of fibrin clots, including size, age, and cellular composition, as well as heterogeneity in endothelial cell function, may modify the participation of uPA in endogenous fibrinolysis